Activation of STING requires palmitoylation at the Golgi - Kojiro Mukai (Nature Portfolio, 2016)
STING is essential for the type I interferon immune response to foreign DNA. Here, the authors show that palmitoylation of STING at the Golgi is required for activating downstream signalling, and increased Golgi localization of certain STING variants may cause autoimmune disease in some cases.